Molecular dynamics simulations of AlN deposition on GaN substrate. (3rd July 2019) - Zhang, Libin; Yan, Han; Sun, Kuan; Liu, Sheng; Gan, Zhiyin
ABSTRACT: In this work, we investigated the deposition of AlN film on GaN substrate by using molecular dynamics (MD) simulations. The effects of GaN substrate surface, growth temperature, and injected N: Al flux ratio on the growth of AlN film were simulated and studied. Consequently, the deposited AlN film on the (0001) Ga-terminated GaN surface achieves better surface morphology and crystallinity than that on the (000-1) N-terminated GaN surface due to the different diffusion ability of Al and N adatoms on two GaN surfaces. Furthermore, with the increase of growth temperature, the surface morphology and crystallinity of AlN film were improved owing to the enhanced mobility of adatoms. At the optimised injected N: Al flux ratio of 1, comparatively good surface morphology and crystallinity of deposited AlN films were realised. This method lays a foundation for the follow-up real-time study of defects and stress evolution of AlN on GaN and can be applied to film growth of other materials. GRAPHICAL ABSTRACT: